Indonesian Government Policy on Restrictions on Exports of Nickel Raw Materials to the European Union - Ronsul, Syeny; Dewi, Ni Made Witari; Sastrini, Luh Ketut Ayu Manik (Formosa Journal of Applied Sciences, 2024)
Indonesia is one of the largest contributors to nickel output in the world. The Indonesian government implemented a nickel export embargo that was previously planned for 2022, advancing to 2020. This government policy aims to increase economic added value, reduce dependence on raw material exports, and provide long-term benefits for the Indonesian economy and society. However, this policy caused dissatisfaction on the part of the European Union, which then sued Indonesia to the WTO with complaint number DS592. This research uses normative legal research methods. The results show that Indonesia does not prohibit the export of nickel that has been processed and refined, so that global nickel producers do not lack raw materials. Indonesia is also obliged to ensure the availability of supplies for domestic needs, especially for smelter players who have invested